Content analysis of research in the context of socio-scientific issues in chemistry learning - Zulkhairi Zulkhairi; Momo Rosbiono; Hernani (Pelita International Publishing, 2024)
This article aims to describe research in the context of socio-scientific issues from 2016 to 2022. The method used is descriptive content analysis method to analyze 30 journal articles of national and international repute. The variables to be analyzed include the method, purpose, year of publication, region, sample, data collection tools, and data analysis techniques. The result showed that most research aims to improve student learning outcomes, interest and motivation to learn. Most of the research methods applied are qualitative and quantitative methods using the experimental class and control class and a small portion using the R&D/Development method. The instruments used were questionnaires, observation sheets and interviews. The data analysis technique used is quantitative analysis technique using statistics (Ancova, Manova, t-test) and qualitative data analysis. Most of the samples consist of students and a small part consists of teachers. This research is spread across Europe, the United States and Asia, with the most publication year being 2021. The issues raised are health and environmental issues related to organic chemistry and environmental chemistry. The most published articles are from the Journal of Chemical Education (JCE) and Journal Science Education (JSE), with the publication years 2021 and 2019.